Conjugated Acetylenic Polymers Grafted Cuprous Oxide as an Efficient Z‐Scheme Heterojunction for Photoelectrochemical Water Reduction. Issue 39 (20th August 2020) - Sun, Hanjun; Dong, Changlin; Liu, Qinglei; Yuan, Yang; Zhang, Tao; Zhang, Jian; Hou, Yang; Zhang, Di; Feng, Xinliang
Abstract: As attractive materials for photoeletrochemical hydrogen evolution reaction (PEC HER), conjugated polymers (e.g., conjugated acetylenic polymers [CAPs]) still show poor PEC HER performance due to the associated serious recombination of photogenerated electrons and holes. Herein, taking advantage of the in situ conversion of nanocopper into Cu2 O on copper cellulose paper during catalyzing of the Glaser coupling reaction, a general strategy for the construction of a CAPs/Cu2 O Z‐scheme heterojunction for PEC water reduction is demonstrated. The as‐fabricated poly(2, 5‐diethynylthieno[3, 2‐b]thiophene) (pDET)/Cu2 O Z‐scheme heterojunction exhibits a carrier separation efficiency of 16.1% at 0.3 V versus reversible hydrogen electrode (RHE), which is 6.7 and 1.4‐times higher respectively than those for pDET and Cu2 O under AM 1.5G irradiation (100 mW cm −2 ) in the 0.1 m Na2 SO4 aqueous solution. Consequently, the photocurrent of the pDET/Cu2 O Z‐scheme heterojunction reaches ≈ 520 µ A cm −2 at 0.3 V versus RHE, which is much higher than pDET (≈ 80 µ A cm −2 ), Cu2 O (≈ 100 µ A cm −2 ), and the state‐of‐the‐art cocatalyst‐free organic or organic‐semiconductor‐based heterojunctions/homojunctions photocathodes (1–370 µ A cm −2 ). This work advances the design of polymer‐based Z‐scheme heterojunctions and high‐performance organic photoelectrodes. Abstract : A conjugated acetylenic polymers (CAPs)/cuprous oxide Z‐scheme heterojunction is fabricated by a general nanocopper‐mediated Glaser polycondensation strategy based on in situ conversion of nanocopper into Cu2 O in the growth of the CAPs. Eventually, the as‐fabricated poly(2, 5‐diethynylthieno[3, 2‐b]thiophene) (pDET)/Cu2 O Z‐scheme heterojunction substantially facilitates charge separation/transfer and exhibits state‐of‐the‐art performance for photoelectrochemical hydrogen evolution.